0.09y+0.09(900-y)=0.50y

Simple and best practice solution for 0.09y+0.09(900-y)=0.50y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.09y+0.09(900-y)=0.50y equation:


Simplifying
0.09y + 0.09(900 + -1y) = 0.50y
0.09y + (900 * 0.09 + -1y * 0.09) = 0.50y
0.09y + (81 + -0.09y) = 0.50y

Reorder the terms:
81 + 0.09y + -0.09y = 0.50y

Combine like terms: 0.09y + -0.09y = 0.00
81 + 0.00 = 0.50y
81 = 0.50y

Solving
81 = 0.50y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-0.50y' to each side of the equation.
81 + -0.50y = 0.50y + -0.50y

Combine like terms: 0.50y + -0.50y = 0.00
81 + -0.50y = 0.00

Add '-81' to each side of the equation.
81 + -81 + -0.50y = 0.00 + -81

Combine like terms: 81 + -81 = 0
0 + -0.50y = 0.00 + -81
-0.50y = 0.00 + -81

Combine like terms: 0.00 + -81 = -81
-0.50y = -81

Divide each side by '-0.50'.
y = 162

Simplifying
y = 162

See similar equations:

| 1.2x-3.3=0.6x-2.58 | | 6x-16=2x+16 | | 5-8n+3n=10-85 | | 5+6=-2-15 | | -3x+1=x+1 | | 9*(-5)= | | 215-33x=33x+15 | | 2(67-3y)=2(67-3y) | | 3(3x+3)-6=3x-3 | | 14-7x=96-21x | | y=x^2+12x-9 | | 12-2a+a+3=0 | | 14x^2+28x+14=0 | | -7x+6+5x=-3x+11 | | 6x^2+15x+27=0 | | 3x-6+6(x+1)=7x+2 | | 10x^2+16x+24=0 | | x+12=2x+5 | | -3x^3-6x=0 | | 2-7(y+2)=9-3y | | -7[5+3(6+9)]= | | (6y^3-y^2+4)(4y^2+y+1)= | | -7x+7+5x=-3x+12 | | 8.5p=7.5p | | -7x+4+5x=-3x+9 | | 0.2(x+1)=0.3(x+11) | | -6(x+1)+2(7x+9)= | | 2x+149=9x-5 | | 9-4(y+7)=7+3y | | x^4+9x^2+400=0 | | 3b-2=19 | | 2x-3+5x=4+4x+1 |

Equations solver categories